Naming Buddha Images and Capitalist Discourse in Thai Society - Prangthong, Nopphadon; Srirut, Kawee (ARU Research Journal Humanities and Social Sciences, 2026)
This qualitative descriptive-analytical study aims 1) to examine patterns and characteristics of naming Buddha images in contemporary Thai society; 2) to analyze the meanings and discourses embedded in such names, particularly those associated with capitalism and consumerism; and 3) to explain the relationship between the naming of Buddha images and contemporary socio-economic and cultural contexts. The study employs documentary analysis and discourse analysis, drawing on data from Buddha image names found in temples, printed materials, and online media in Thailand. The findings indicate that (1) the naming of Buddha images in contemporary Thai society tends to emphasize worldly outcomes, such as wealth, success, immediacy, and practical problem-solving; however, these meanings often coexist with enduring spiritual dimensions rooted in traditional Buddhist beliefs; (2) Such names may function as discursive elements that reflect, and in some cases reproduce, aspects of capitalist and consumerist logic by positioning religion as a symbolic resource connected to devotees’ expectations. These meanings do not exist in isolation but overlap with and coexist alongside spiritual and philosophical religious discourses; and (3) The naming of Buddha images constituted a site of meaning negotiation among Buddhism, capitalist culture, and beliefs prevalent in Thai society, thereby reflecting the adaptation of religion to the uncertainties of contemporary life. The study recommends promoting critical awareness of the roles of language and religious discourse and developing forms of religious communication that maintain a balance between responding to contemporary social contexts and preserving the core teachings of Buddhism.